"Doll #135 with vitiligo": Are alopecia and vitiligo Barbie worth the hype?. Issue 5 (21st July 2020) - Shah, Syed Fazal Hussein
Abstract: Toy manufacturer Mattel released a new line of diverse Barbie dolls earlier this year, including dolls with alopecia and vitiligo. The new dolls have been widely celebrated, with both media and dermatologists proposing that the dolls could provide significant benefits for the low self‐esteem and societal exclusion suffered by children with similar dermatoses. However, the reality may be very different. Here, we present existing research on the impact of diverse dolls on children's play and psychology to argue that the dolls' proposed benefits for children with alopecia and vitiligo are unlikely to materialize; rather, alopecia and vitiligo Barbie could prove more harmful than beneficial.